Endometrial oxytocin binding sites in normal women and in subfertile patients. Issue 773 (March 1990) - Baker, P. N.; Peat, M. L.; Symonds, E. M.; Maynard, P. V.
Abstract : Specific binding of oxytocin to high affinity sites in endometrial membrane preparations has previously been shown in sheep. Endometrial tissue preparations from 27 'normal' women of proven fertility were incubated with tritiated oxytocin and the existence of significant binding sites in human endometrium was shown. Furthermore, the level of binding sites underwent a cyclical variation with the highest concentration of binding at midcycle. A cyclical pattern of binding site concentration not unlike that found in the normal women was shown in 19 subfertile patients taking clomiphene. However, in 20 subfertile patients not taking clomiphene, no cyclical pattern emerged with significantly lower levels of binding sites in the mid-portion of the cycle (P less than 0.02) and significantly higher levels in the mid-late luteal phase (P less than 0.01), as compared to the normal women. In the mid-portion of the cycle levels were significantly lower in the subfertile patients not taking clomiphene (P less than 0.03) as compared to those taking clomiphene. No significant differences were shown between the normal women and those patients taking clomiphene.